2018
DOI: 10.3389/fendo.2018.00600
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Immune Disorders in Combined Endocrine Pathology

Abstract: Introduction: Combined endocrine pathology is a serious healthcare problem in Ukraine. This prospective study assessed the blood levels of 25-hydroxyvitamin D [25(OH)D] and markers of immune function in response to vitamin D intervention in patients with type 1 and type 2 diabetes mellitus (T1DM and T2DM, respectively) and autoimmune thyroiditis (AIT).Objective: This study evaluated the relationship between the metabolic and immune status of DM + AIT patients with respect to their vitamin D status and changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
0
19
0
6
Order By: Relevance
“…Deficiencies of both vitamins may play a role in the pathogenesis of T1DM. 18,19 Giulietti et al reported the overexpression of pro-inflammatory cytokines, reduced thymus performance and pancreatic islet dysfunction in non-obese diabetic mice kept away from ultraviolet light and fed with a vitamin D-depleted diet. 20 In a Finnish birth cohort study, Hyppönen et al found that daily supplementation of 200 IU of vitamin D was associated with a lower incidence of T1DM among children.…”
Section: Association Of Bioactive Molecules With Breastfeedingmentioning
confidence: 99%
“…Deficiencies of both vitamins may play a role in the pathogenesis of T1DM. 18,19 Giulietti et al reported the overexpression of pro-inflammatory cytokines, reduced thymus performance and pancreatic islet dysfunction in non-obese diabetic mice kept away from ultraviolet light and fed with a vitamin D-depleted diet. 20 In a Finnish birth cohort study, Hyppönen et al found that daily supplementation of 200 IU of vitamin D was associated with a lower incidence of T1DM among children.…”
Section: Association Of Bioactive Molecules With Breastfeedingmentioning
confidence: 99%
“…Зважаючи на плейотропні ефекти вітаміну D в людському організмі [41][42][43], продовжується вивчення ролі його недостатності в патогенезі багатьох метаболічних порушень, включаючи ожиріння, ЦД-2 та СПКЯ.…”
Section: роль вітаміну D в патогенезі спкя та його кардіометаболічнихunclassified
“…При цукровому діабеті 1 типу організм не виробляє інсулін, що призводить до необхідності щоденних його ін'єкцій (Dedov, 2000;Dedov et al, 2001;Zorin, 2005;Shakhbazidi et al, 2006). Проте тривале використання замінної терапії та гіпоглікемічних препаратів може призвести до інсулінорезистентності, а також не запобігає розвиток макро-і мікроваскулярних ускладнень (Kovalska, 2000;King et al, 2003;Komisarenko et al, 2003).…”
Section: вступunclassified